2022
DOI: 10.47391/jpma.3867
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with undernutrition among 6-59 months children in Tehsil Battagram, Pakistan

Abstract: Objective: To find out the prevalence and associated factors of undernutrition in a semi-rural setting. Method: The community-based cross-sectional study was conducted in Tehsil Battagram of Khyber Pakhtunkhwa province, Pakistan, in January and February 2020 after approval from the ethics review committee of Nanjing Medical University, Jiangsu, China, and comprised children aged 6-59 months who had no physical or mental disability. Data was collected using a structured questionnaire. Anthropometric data was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Research has shown that neonatal intensive care unit (NICU) parents are concerned about the experiences of pain and their infants experience. Research has described that parents would like more information about painful procedures, how they could be involved in managing their infants pain and are concerned about the impact of pain on the parent-infant relationship (Ahmad et al, 2022; Franck et al, 2005). Parents would like to take an active role in pain management and there is evidence to support the importance of parental involvement in this (Palomaa et al, 2016; Skene et al, 2012; Ullsten et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that neonatal intensive care unit (NICU) parents are concerned about the experiences of pain and their infants experience. Research has described that parents would like more information about painful procedures, how they could be involved in managing their infants pain and are concerned about the impact of pain on the parent-infant relationship (Ahmad et al, 2022; Franck et al, 2005). Parents would like to take an active role in pain management and there is evidence to support the importance of parental involvement in this (Palomaa et al, 2016; Skene et al, 2012; Ullsten et al, 2021).…”
Section: Introductionmentioning
confidence: 99%